Capture and Ideology in the Economic Theory of Politics - Kalt, Joseph P.; Zupan, Mark A. (American Economic Review, 1984)
The economic theory of regulation long ago put public interest theories of politics to rest. These theories have correctly been viewed as normative wishings, rather than explanations of real world phenomena. They have been replaced by models of political behavior that are consistent with the rest of microeconomics (Anthony Downs, 1957; James Buchanan and Gordon Tullock, 1965; George Stigler, 1971; Sam Peltzman, 1976). Recently, however, debate has arisen over whether some version of a public interest theory of regulation will have to be readmitted to our thinking about actions and results in the political arena. What is at issue is the empirical importance of the altruistic, publicly interested goals of rational actors in determining legislative and regulatory outcomes (James Kau and Paul Rubin, 1979; Kalt, 1981; Peltzman, 1982). This study assesses the nature and significance of publicly interested objectives in a particular instance of economic policymaking: U.S. Senate voting on coal strip-mining regulations. The existence of such objectives is, of course, no contradiction of the economic view of human behavior (Kenneth Arrow, 1972; Gary Becker, 1974); and may well be rooted in genetic-biological history (Becker, 1976; Jack Hirshleifer, 1978). Generally, however, individuals' altruistic, publicly interested goals have been given little attention. This reflects the judgment that such goals are so empirically unimportant as to allow the use of Occam's razor in positive models, or well-founded apprehensions that these goals are unusually difficult to identify, measure, and analyze. Notwithstanding the latter problem, we find that approaches which confine themselves to a view of political actors as narrowly egocentric maximizers explain and predict legislative outcomes poorly. The tracking and dissecting of the determinants of voting on coal strip-mining policy suggest that the economic theory of politics has been prematurely closed to a broader conception of political behavior.